Factors Influencing Vocabulary Learning Difficulties Among Students in Inclusive English Classroom: An English Teacher’s Perception - Tisya Amalia Putri Sitorus; Yani Lubis (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates the factors influencing students’ limited vocabulary knowledge as an observable manifestation of vocabulary learning difficulties (VLD) in an inclusive English classroom. Vocabulary learning difficulties remain a significant challenge in EFL contexts, particularly in classrooms with diverse learning needs. This study aims to explore how these difficulties are perceived and addressed from the perspective of an English teacher. A qualitative descriptive case study design was employed, involving one English teacher in a Grade 7 inclusive classroom at an Islamic integrated junior high school in Medan. Data were collected through a semi-structured interview and classroom observations and analyzed using thematic analysis. The findings reveal that vocabulary learning difficulties are shaped by the interaction between internal and external factors. Internally, students’ motivation, memory, learning interest, and individual learning pace significantly affect their ability to retain and use vocabulary. Students with limited vocabulary foundations experience difficulties in memorizing, pronouncing, and expressing vocabulary, particularly in speaking and translating activities. Externally, instructional practices, classroom conditions, and exposure to English influence vocabulary development. Although the teacher applied supportive strategies such as repetition, contextualization, and direct practice, challenges such as limited use of visual media, diverse student needs, and time constraints hindered optimal vocabulary learning. The study highlights that vocabulary learning difficulties in inclusive classrooms should be understood as a contextual and interactional phenomenon rather than solely as individual deficits. These findings emphasize the importance of adaptive teaching strategies and supportive learning environments in addressing vocabulary learning difficulties.